Reference range of fetal splenic circumference from 14 to 40 weeks of gestation - Kasemsri Srisupundit (2018)
Objective: To create a nomogram for fetal splenic circumference of normal fetuses. Materials and methods: A prospective, cross-sectional study was undertaken on normal pregnancies with certain date from 14 to 40 weeks of gestation. All fetuses were measured for fetal splenic circumference by tracing technique on transverse view of the fetal abdomen, using high-resolution real-time ultrasound with a 2-4 MHz convex transducer. Results: A total of 684 normal pregnant women between 14 and 40 weeks of gestation were recruited. Fifty-eight were excluded because of poor image quality and fetal abnormality. The remaining 626 were available for analysis. Quadratic equation model was best fitted to estimate the 5th, 50th and 95th percentile range of splenic circumference at each gestational week. Fetal splenic circumference was gradually increased with gestational age with fitted equation as follows: splenic circumference (cm) = -4.181 + 0.456 (GA) -0.001 (GA)2 (r = 0.942, p < 0.001). The table of nomogram for various percentile ranges was constructed. Conclusion: A normal reference range of fetal splenic circumference for each week of gestational age during 14-40 weeks is established. © 2010 Springer-Verlag.